Upaya swamedikasi tanaman obat keluarga untuk mengatasi gejala dispepsia - Azzahra, Fatimah (Maliki Interdisciplinary Journal, 2023)
Self-medication is a form of taking medicines, herbs or home remedies on your own initiative without consulting a doctor first. Self-medication can be done by utilizing plants that have medicinal properties as an alternative to the process of overcoming disease complaints. Dyspepsia is a type of non-communicable disease that can be treated through self-medication or self-medication if the symptoms are not too severe. Dyspepsia has symptoms of pain or discomfort in the upper abdomen or solar plexus. The purpose of this article is to provide an understanding regarding self-medication to the community in overcoming dyspepsia with non-pharmacological therapies using herbal plants that have medicinal properties and healthy living behaviors using qualitative methods through a literature study approach. Symptoms of dyspepsia can be overcome by self-medication (self-medication) through non-pharmacological therapy, namely consuming traditional herbal medicine by utilizing family medicinal plants, besides that it must also be balanced by changing a healthy lifestyle. The results showed that family medicinal plants that can treat dyspepsia include: turmeric (Curcuma longa), black cumin (Nigella sativa), ginger (Zingiber officinalis), black grass jelly (Mesona palutris), and peppermint leaves (Mentha piperata).